Field Survey on Maritime Literacy and Seaweed Food Security in Community Service Initiatives Informed by Folklore - Rumalean, Iwan; Rachman, Gazali; Kurniawan, Sabda Aji; Sampulawa, Firsya Fadilah; Halim, Arif Nur; Supriyono, Areni Yulitawati (Universitas Negeri Semarang, 2025)
Coastal communities in Eastern Indonesia, particularly in the 3T (frontier, outermost, disadvantaged) regions, face complex challenges in managing abundant marine resources despite their cultural richness and ecological potential. This study was conducted in Waiheru Village, Ambon, which represents a coastal community where traditional maritime folklore remains a living heritage yet has not been optimally integrated into food security strategies. The research aimed to explore the level of maritime literacy and the utilization of seaweed for household food resilience by mapping the potentials and problems faced by women and youth as primary community actors. A qualitative field survey was carried out involving 60 respondents consisting of housewives and village youth, using open-ended questionnaires, semi-structured interviews, and direct observation. Thematic analysis revealed that folklore, such as the Nenek Luhu legend, can serve as an effective medium for strengthening ecological awareness and maritime identity. Findings indicated that housewives are central in basic seaweed processing for household consumption, but their skills remain limited to low-value products, while youth show strong interest in digital-based promotion despite constraints in technical capacity and internet access. This research contributes to science by offering an integrative model that links culture, ecology, and community-based economy as a foundation for sustainable coastal development.